2022
DOI: 10.1055/a-1774-4736
|View full text |Cite
|
Sign up to set email alerts
|

Direct percutaneous endoscopic jejunostomy (DPEJ) and percutaneous endoscopic gastrostomy with jejunal extension (PEG-J) technical success and outcomes: Systematic review and meta-analysis

Abstract: Background and study aims Endoscopic methods of delivering uninterrupted feeding to the jejunum include direct percutaneous endoscopic jejunostomy (DPEJ) or PEG with jejunal extension (PEG-J), validated from small individual studies. We aim to perform a meta-analysis to assess their effectiveness and safety in a variety of clinical scenarios. Methods Major databases were searched until June 2021. Efficacy outcomes included technical and clinical success, while safety outcomes included adverse events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
6
0
2
Order By: Relevance
“…Technical failures are reported mostly because of limited enteroscope advancement in patients with a history of abdominal surgery and adhesions. DPEJ by DAE has a significant adverse event rate of 3.5 % [273][274][275][276]; these include bleeding and SB perforation. DAE-assisted PEJ can represent an alternative to surgical jejunostomy according to local availability and expertise.…”
Section: Dae-assisted Percutaneous Endoscopic Jejunostomy (Pej) For E...mentioning
confidence: 99%
“…Technical failures are reported mostly because of limited enteroscope advancement in patients with a history of abdominal surgery and adhesions. DPEJ by DAE has a significant adverse event rate of 3.5 % [273][274][275][276]; these include bleeding and SB perforation. DAE-assisted PEJ can represent an alternative to surgical jejunostomy according to local availability and expertise.…”
Section: Dae-assisted Percutaneous Endoscopic Jejunostomy (Pej) For E...mentioning
confidence: 99%
“…Buneo et al reported a case series of DPEJ in esophagectomy patients with overall low incidence PEJ related complications 15 . Recent metanalysis has investigated DPEJ and PEG-J across several patient populations with limited numbers of RYGB included within these studies 23 . Al-Bawardy et al included 17 RYGB patients in their 94-patient single center study, Strong et al included 19 RYGB patients in their 59 cases, and Wong Kee Song et al included two RYGB in their cohort of 33 patients 4 12 24 .…”
Section: Discussionmentioning
confidence: 99%
“…With the growing number of patients receiving bariatric surgeries within the US, our study demonstrates that DPEJ can be successfully performed in RYGB. Endoscopic driven enteral feeding tube placement more often has shorter procedure times, less cost, less exposure to anesthesia, and quicker recovery time when compared to surgery 23 . The low procedural failure rate (11%) was secondary to appropriate parameters to avoid endoscopic placement given inability to find ideal transillumination or an inflamed jejunum unsuitable for DPEJ placement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations